Provision of Escrow Services at the Absence of an Agreement: The Assessment for Compliance with the Russian Law - Vasilevskaya, Liudmila Yu.; Rozhkova, Marina A. (Cuestiones Políticas, 2020)
Based on an analysis of the norms of the Civil Code of the Russian Federation, the authors studied the legal basis for the provision of a range of services by the online classified in the digital environment. Additionally, the authors studied the structure of relations arising between the buyer, seller, online classified, delivery service, and the bank. The article substantiates that there is a conditional escrow of property in the framework of the considered relations, but the fact of concluding an agreement creating an appropriate legal basis for such an escrow is not observed. The study results identify several civil law agreements, needed for the goods delivery services offered by online classifieds. The authors concluded that the relationship system built by the online classified with sellers, buyers, a delivery service, and a bank and providing for the reservation of the buyer’s money excludes the conclusion of an escrow agreement.